TRANSPORT-CONTROLLED KINETICS OF DISSOLUTION AND PRECIPITATION IN THE SEDIMENTS UNDER ALKALINE AND SALINE CONDITIONS - Qafoku N.P.; Ainsworth C.C.; Szecsody J.E.; Qafoku O.S. (My University, 2004)
Over 1.6 million liters of radioactive, high-temperature, Al-rich, alkaline and saline high-level waste (HLW) fluids were accidentally discharged from tank leaks onto the sediments at the Hanford Site, Washington. In order to better understand processes that might occur during the migration of HLW through sediments and to estimate their extents, we studied the effects of Al-rich, alkaline and saline solutions on soil mineral dissolution and precipitation during reactive transport. Metal- and glass-free systems were used to conduct miscible-displacement experiments at 50 °C under CO2 and O2 free conditions. Results showed significant release of Si, K, Al, Fe, Ca, Mg, and Ba into the aqueous phase. The transport-controlled release of these elements was time dependent as evidenced by its extent varying with the fluid residence time. Silica initial dissolution rates (6.08 × 10-11 and 5.38 × 10-13 mol m-2 s-1) increased with base concentration, decreased with Al concentration, and decreased with fluid residence time. Aluminum precipitation rates varied in the range from 0.44 to 1.07 × 10-6 mol s-1 and were faster in these column experiments than in previous batch studies. The initial rate constant of Al precipitation reaction was 0.07 h-1 (half-life of 9.9 h at about 3 PV); it increased up to 0.137 h-1 (half-life of 5.1 h at about 20 PV). The precipitates identified with SEM and suggested from the modeling results were mainly NO3-cancrinite. SEM analyses also indicated the formation of sodalite when Al was not present in the leaching solution. In addition, results from modeling suggested the precipitation of brucite, goethite and gibbsite; the latter may precipitate in the presence of high Al concentrations. Aqueous and solid phase transformations caused by base-induced dissolution and subsequent secondary phases precipitation should be important determinants of the fate of contaminants and radionuclides in the vadose zone under alkaline and saline conditions.